Encouraging 5-year olds to attend to landmarks: a way to improve children's wayfinding strategies in a virtual environment - Lingwood, Jamie; Blades, Mark; Farran, Emily K.; Courbois, Yannick; Matthews, Danielle (Frontiers in Psychology, 2015)
Wayfinding can be defined as the ability to learn and remember a route through an environment. Previous researchers have shown that young children have difficulties remembering routes. However, very few researchers have considered how to improve young children’s wayfinding abilities. Therefore, we investigated ways to help children increase their wayfinding skills. In two studies, a total of 72 5-year olds were shown a route in a six turn virtual environment and were then asked to retrace this route by themselves. A unique landmark was positioned at each junction and each junction was made up of two paths: a correct choice and an incorrect choice. Two different strategies improved route learning performance. In Experiment 1, verbally labelling landmarks at junctions during the first walk reduced children’s errors at turns, and the number of trials they needed to reach the learning criterion. In Experiment 2, encouraging children to attend to landmarks at junctions on the first walk reduced the children’s errors when making a turn. This is the first study to show that very young children can be taught effective route learning skills.